Reorganized Brain Functional Network Topology in Presbycusis - Guan, Bing; Xu, Yixi; Chen, Yu-Chen; Xing, Chunhua; Xu, Li; Shang, Song'an; Xu, Jin-Jing; Wu, Yuanqing; Yan, Qi (Frontiers in Aging Neuroscience, 2022)
Purpose: Presbycusis, characterized by bilateral sensorineural hearing loss at high frequencies, and is often accompanied by cognitive decline. This study aimed to identify topological reorganization of brain functional network in presbycusis with/without cognitive decline by using graph theory analysis approaches based on resting-state functional magnetic resonance imaging. Methods: Resting-state functional magnetic resonance imaging (rs-fMRI) scans were obtained from 30 presbycusis patients with cognitive decline, 30 presbycusis patients without cognitive decline and 50 age-, sex-, and education-matched healthy controls. Graph theory was applied to analyze the topological properties of brain functional networks including global and nodal metrics, modularity and rich club organization. Results: At the global level, the brain functional networks of all participants were found to possess small-world properties. And significant group difference in global network metrics were observed among the three groups such as clustering coefficient, characteristic path length, normalized characteristic path length, and small-worldness. At the nodal level, several nodes with abnormal betweenness centrality, degree centrality, nodal efficiency and nodal local efficiency were detected in presbycusis patients with/without cognitive decline. Changes in intra-modular connections in frontal lobe module and inter-modular connections in prefrontal subcortical lobe module were found in presbycusis patients exposed by modularity analysis. Rich club nodes were reorganized in presbycusis patients, while the connections among them had no significant group differences. Conclusion: Presbycusis patients exhibited topological reorganization of the whole-brain functional network and presbycusis patients with cognitive decline showed more obvious changes in these topological properties than those without cognitive decline. Abnormal changes of these properties in presbycusis patients may compensate for cognitive impairment by mobilizing additional neural resources.